Role of Microglial Cells in Alzheimer’s Disease Tau Propagation - Španić, Ena; Langer Horvat, Lea; Hof, Patrick R.; Šimić, Goran (Frontiers in Aging Neuroscience, 2019)
It is well known that uncontrolled immune response in the brain contributes to the progression of neurodegenerative diseases and more particularly Alzheimer's disease. Recent investigations have documented the prion-like features of tau protein and the involvement of microglial changes upon tau pathology. While it is still unclear what sequence of events is causal, it is likely that tau seeding potential and microglial contribution to tau propagation act together, and are essential for the development and progression of degenerative changes. Based on available evidence, targeting tau seeds and controlling some signaling pathways in a complex inflammation process could represent a possible new therapeutic approach for treating neurodegenerative diseases. Recent findings propose novel diagnostic assays and markers that may be used together with standard methods to complete and improve the diagnosis and classification of these diseases. In conclusion, a novel perspective on microglia-tau relations reveals new issues to investigate and imposes different approaches for developing therapeutic strategies.